Small Dam Safety - World Bank (World Bank, Washington, DC, 2021)
Small dams play an important role in the provision of many kinds of benefits, such as drinking and irrigation water supply, flood control, small/mini hydropower generation, fishing, and so on. They are particularly important in rural and agricultural areas. Agriculture remains an engine of rural growth and poverty reduction in developing countries. Agricultural water management (AWM) can change the lives of millions of people by improving yields, reducing risks linked to climate variability, and increasing income for farmers. The demand for water storage is increasing as farmers and rural communities are more frequently facing water shortages for their crops and livestock. This demand is in part driven by climate change and increasing variability and scarcity observed around the globe. This note provides some lessons on how to address the challenges of small dam management with participation of community groups and effective government support for them.